THE TENDENCY TO ANOREXIA NERVOSA WITH THE INCIDENCE OF BODY DYSMORPHIC DISORDER AND ITS MEDICAL EMERGENCIES - Diona Ossy Wahyuni (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Background: Anorexia nervosa (AN) and body dysmorphic disorder (BDD) are severe body image disorders that severely interfere with the daily functioning of the individual. They are separate but overlapping nosological entities. In this review, we will explain the meaning between AN and BDD and the prevalence of the incidence of these two problems and discuss the clinical implications that may occur in the future.Â Methods: The researcher used several literature and scientific journals, which was based on 15 journals and literature, discussing a tendency to anorexia nervosa with the incidence of Body Dysmorphic Disorder and its medical emergencies.Â Conclusion: There is a correlation of anorexia nervosa among teenager especially girl teenage.Â